Dampak Sosial Budaya Pariwisata: Studi Kasus Desa Wisata Pulesari dan Desa Ekowisata Pancoh - Rohani, Elisa Dwi; Irdana, Nuryuda (Jurnal Master Pariwisata (JUMPA); Volume 08, Nomor 01, Juli 2021, 2021)
Tourism can be seen not only as an economic phenomenon, but also as a socio-cultural phenomenon. Tourism is a phenomenon of cultural interaction which ultimately affects the cultural changes and behavior of local people as tourism actors. This study aims to provide a different picture related to the impact of tourism by presenting an overview of the socio-cultural life of the community after tourism activities in tourist villages. In this study using a comparative study method. The positive impacts that occur between the two villages are very different in social aspects, namely: 1) The spirit of the community that naturally awakens in the Pulesari tourist village, 2) strengthening organization (strengthening the organization), 3) the emergence of leaders (the emergence of leaders). While the negative impacts from the social aspect include 1) the impact that occurs in the community (Community Division) 2) social problems (social problems) related to drugs or prostitution, 3) Conflicts begin to emerge in the form of the emergence of new tourist villages that carry the same concept. Cultural events that occur include 1) preservation of local culture (preservation of local culture), 2) exchange of information between hosts and guests regarding village potential, arts, traditions, customs, patterns, patterns of life and culture that lead to deeper interactions. While the negative impacts that occur include 1) commercialization of culture, 2) imitating other cultures (imitating other cultures). Keywords: Impact, Socio-cultural, Tourism, Tourism Village